2021
DOI: 10.1093/jjco/hyaa266
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of subsequent molecular targeted therapy after immuno-checkpoint therapy, retrospective study of Japanese patients with metastatic renal cell carcinoma (AFTER I-O study)

Abstract: Objectives Guidelines for treatment of mRCC recommend nivolumab monotherapy (NIVO) for treated patients, and nivolumab plus ipilimumab combination therapy (NIVO+IPI) for untreated IMDC intermediate and poor-risk mRCC patients. Although molecular-targeted therapies (TTs) such as VEGFR-TKIs and mTORi are recommended as subsequent therapy after NIVO or NIVO+IPI, their efficacy and safety remain unclear. Methods Outcome of Japane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 44 publications
2
18
0
Order By: Relevance
“…Most of the outcomes of subsequent therapy observed in pivotal clinical trials are insufficient, and long-term follow-ups and observational studies of subsequent therapy in real-world settings are needed for decision-making regarding treatment strategies. Consistent with previous reports on the outcomes of subsequent therapy after NIVO or immuno-oncology (I-O) combination therapy ( 5–21 ), we have also reported favorable anti-tumor activity of TT after the discontinuation of NIVO or NIVO+IPI in mRCC patients in Japanese real-world settings in the ‘AFTER I-O study’ ( 22 ).…”
Section: Introductionsupporting
confidence: 91%
“…Most of the outcomes of subsequent therapy observed in pivotal clinical trials are insufficient, and long-term follow-ups and observational studies of subsequent therapy in real-world settings are needed for decision-making regarding treatment strategies. Consistent with previous reports on the outcomes of subsequent therapy after NIVO or immuno-oncology (I-O) combination therapy ( 5–21 ), we have also reported favorable anti-tumor activity of TT after the discontinuation of NIVO or NIVO+IPI in mRCC patients in Japanese real-world settings in the ‘AFTER I-O study’ ( 22 ).…”
Section: Introductionsupporting
confidence: 91%
“…Second‐line TKI treatment after failure of first‐line nivolumab and ipilimumab showed an ORR of 36% and a median PFS of 7–8 months 24 . The ORR of TKI after nivolumab was 27% with a median PFS of 8.9 months in a separate retrospective study 25 . The efficacy of salvage ICI/TKI in ICI‐pretreated patients was reported in a Phase II study, which demonstrated an ORR of 55.8% and a median PFS of 12.2 months by pembrolizumab and lenvatinib 26 .…”
Section: Discussionmentioning
confidence: 80%
“… 24 The ORR of TKI after nivolumab was 27% with a median PFS of 8.9 months in a separate retrospective study. 25 The efficacy of salvage ICI/TKI in ICI‐pretreated patients was reported in a Phase II study, which demonstrated an ORR of 55.8% and a median PFS of 12.2 months by pembrolizumab and lenvatinib. 26 Although some individual patients might achieve relatively longer PFS, both ORR and PFS seem to fall short by salvage nivolumab and ipilimumab therapy, compared with TKI‐incorporated therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, patients after NIVO + IPI are naïve for VEGFR-TKIs. Tomita et al [19] reported that the ORR and median PFS of VEGFR-TKIs after NIVO + IPI were 32% and 16.3 months, respectively. Auvray et al [20] reported that the median PFS of sunitinib after NIVO + IPI was 11 months.…”
Section: Discussion/conclusionmentioning
confidence: 99%